Does Meaning Make Teams Work? - Idil Bozay (Junior Management Science (JUMS), 2022)
Meaning is a major concern of humans and work is no exception. Economics has long considered the work a mere effort-income exchange and underlooked the importance of meaning in work. Although the meaningful work literature gained momentum in the last years, the research focused on the individual outcomes of meaningful work, such as work satisfaction or reservation wage. Today any modern organization relies on teamwork, so identifying the conditions that enhance cooperation is essential. This study addresses the research gap in the literature by assessing the impact of meaningful work on cooperativeness and discusses its components: self and others, job design and job mission. Furthermore, the study hypothesizes that meaningful work enhances cooperation, and proposes an experimental design utilizing the public goods game with a meaningful work treatment using a donation mechanism.
Keywords: 650; Meaningful work; public goods game; cooperation; experimental economics